Síntese e caracterização de nano-compósito à base de ferritas nanométricas, quitosana e hidroxiapatita para tratamento de câncer de mama - Martins, Murillo Longo [UNESP] (2015)
Breast cancer is one for the biggest wordwide health problems. In Brazil, 58,000 new cases of such a disease are expected to be diagnosed between 2014 and 2015. These tumors require additional concerns due to their great tendency in generating metastasis. In these cases, there is considerable chance for the cancer cells to migrate to the bone tissue. Such a behavior is most likely due to the affinity between the breast cancer cells and hydroxyapatite, the main inorganic component of bones. This work aimed to synthesize a nanomposite containing this compound in order to explore such affinity in the treatment of these tumors. Additionally to the apatite, magnetic nanoparticles have been incoporated to the nanomposite, aiming to combine possible applications on both cancer treatment (magnetic drug delivery and magnetic hyperthermia approaches) and diagnosis [contrast generation in magnetic resonance imagine (MRI) and alternate current biosusceptormetry (ACB) exams]. The obtained nanocomposite is composed by magnetic nanoparticles of Mn-Zn ferrites, with general formula Mn(1-x)ZnxFe(2-y)O4, coated with the polymer chitosan modified by apatite nanocrystals. Aiminf the application of this system as an anti-tumor drug delivery tool for breast cancer treatment, the drug paclitaxel has also been incoporated to the material. The nanocomposite was characterized after each synthesis with the following solid state physics techniques: X-ray and neutron powder diffraction (XRD and ND) with structure refinement by the Rietveld method, scanning electron microscopy (SEM), infrared spectroscopy (FTIR), near edge X ray absorption spectroscopy (NEXAFS), scanning transmission X ray microscopy (STXM), inelastic neutrons scattering (INS) and magnetic characterization. By means of in vitro tests, the cytotoxicity of the materials in healthy cells (NIH/3T3) as well as their association to breast tumor cells (MCF7) were evaluated. The results show that...